Mafia Tanah di Indonesia: Tinjauan Hukum dan Pemberantasannya - Amin, A. Miftahul (Universitas Widya Gama Malang, 2024)
The regulation of land mafia eradication in Indonesia in positive law applicable in Indonesia has been regulated in the codification of Criminal Law, Civil Law, and Administrative Law, where all of them also apply procedural law in the framework of legal efforts in the settlement of land mafia eradication in Indonesia, both non-litigation/Alternative Dispute Resolution (ADR) settlement efforts involving mediators, adjudicators, conciliators, and arbitrators, as well as litigation involving parties/law enforcement agencies ranging from the police, prosecutors, to the court. In the level of practice on the legal consequences of the prevention and eradication of land mafia in Indonesia, in this case there is a significant positive legal effect on the legal efforts to prevent and eradicate the land mafia in Indonesia although it must continue to be improved both in terms of more specific laws and regulations, or in the spirit of law enforcement and land administration bureaucracy/land policy officials.